Experimental researches of heat exchange processes in vertical ventilated channels - Lymarenko, Oleksiy (Technology audit and production reserves, 2019)
The object of research is the processes of heat and mass transfer in open walling, simulated in the climate chamber to reduce heat loss. The work analyzes these processes, which will reduce heat loss through the structural elements of the house during the cold season, as well as reduce the heat input in the warm period. The study of temperature distribution in vertical open enclosing structures was performed on an experimental stand. From the obtained data, it follows that the temperature in open enclosing structures is 1.5-2 °C higher than in normal ones, but the humidity decreases significantly. It can be concluded that moisture in external non-ventilated enclosing structures begins to accumulate on average at the end of the year, that is, with the onset of the cold period –in November or December. And for three or four months, it takes the maximum value and then the construction begins to dry. However, the determination of the annual moisture distribution of the enclosing structure during the year still does not answer the question of how moisture behaves in the thickness of the layers of the multilayer structure. Ventilated enclosing structures significantly affect the distribution of moisture inside the wall. When air comes into contact with the cold surface of the channel, condensation may occur under certain conditions. The surface layers of the channel are dried, but moisture can penetrate into the layers of the structure. During the research it was possible to establish that a significant decrease in moisture in open enclosing structures allows us to avoid pathogens that develop very quickly in a humid environment. There is also the possibility of using heated air in the future in residential areas. In the process of research, the deficiencies of existing methods were eliminated, namely: when using the heat balance equation on the outer surface of the roof, the concept of “equilibrium temperature” is used, it does not always correctly describe the process of heat exchange on the outer surfaces of open enclosing structures.